The immune system of marine invertebrates: Earliest adaptation of animals - R. Bharathi Rathinam; Arpit Acharya; A. Jancy Robina; Husne Banu; Gayatri Tripathi (Comparative Immunology Reports)
The present article provides insights into the immunity of ocean invertebrates. Research in this field has revealed hallmark components and strategies of the animal immune system, which have both theoretical and practical utility. From phylum Porifera to arthropods, animal immunity has evolved over various timescales. Within these timescales, dynamic environmental factors and microbial influences have shaped invertebrate immunity in an adaptive manner, resulting in the acquisition of complex genetic traits. These genetic traits play a crucial role in coding for multiple components, including antigens binding to cellular and cytoplasmic receptors, antimicrobial peptides, proteases, and proteins in pioneer animals. Marine invertebrates, such as sponges, cnidarians, mollusks, echinoderms, and crustaceans, exhibit diverse innate immune mechanisms influenced by their environment and microbial interactions. Despite lacking adaptive immune responses, marine invertebrates rely primarily on innate immunity. Their immune system encompasses physical and chemical barriers that prevent pathogen entry, as well as specialized cells and humoral factors that combat infections and minimize potential damage. In summary, this review explores the immunity of ocean invertebrates, highlighting key discoveries related to both cellular and humoral defenses across various marine species.